5510 sayılı kanun kapsamında m. 4/ 1 (a) bendi̇ gereği̇ si̇gortalı sayılanların si̇gortalılığı - Bal, Resulhan (My University, 2023)
Sosyal Güvenlik Kanunu ile ilgili temel kavramlar, 5510 sayılı Kanunun m.4/ 1 (a) bendi uyarınca sigortalı sayılanlar, bu sigortalıların sigortalılıklarının başlangıcı, bildirimi ve sona ermesi, m.4/ 1 (a) bendi gereği sigortalı sayılanların isteğe bağlı sigortalılık, hizmet borçlanması, hizmet birleştirmesi ve sigortalılık hallerinin çakışması durumlarından hangi şartlarda yararlanacakları ve yararlanmaları halinde ne gibi hukuki sonuçların ortaya çıkacağı açıklanmaktadır.

Basic concepts related to Social Security Law, insured numbers in accordance with Article 4/ 1 (a) of Law No. 5510, the beginning, notification and termination of the insurance period of these insured persons, and the optional insurance of those who are considered insured in accordance with Article 4/ 1 (a) of Law No. 5510, it is explained under which conditions will they benefit from services borrowing, unification of services and overlapping insurance situations and what legal consequences will arise iftheybenefit.
Insurance of those who are insured pursuant to article 4/ 1 (a) under the scope of law numbered 5510
Keywords: Conflict of insurance statuses; Hizmet birleştirilmesi; Hizmet borçlanması; Hukuk ve mevzuat; Insurance law; Insured; İsteğe bağlı sigortalılık; İş sözleşmesi; Law and legislation; Optional insurance; Service combination; Service debt; Sigorta hukuku; Sigortalı; Sigortalılık hallerinin çakışması Employment contract; Social security; Sosyal güvenlik; Turkey; Türkiye